Lope de Vega, El príncipe despeñado. A critical and annotated edition of the autograph manuscript by Henry W. Hogue. Indiana University Press, Bloomington, Indiana, 1955; 188 pp. - Rozzell, Ramón (El Colegio de México, 1958)
Se reseñó el libro: El príncipe despeñado. A critical and annotated edition of the autograph manuscript by Henry W. Hogue.